Evaluation of tomato (Lycopersicon Esculentum Miller) varieties for nematode and ralstonia diseases resistance and productivity - Alemu Tsega Alene; Zelalem G Mariam (Open Journal of Plant Science - Peertechz Publications, 2021)
Tomato is one of the most remunerable and widely grown vegetables in the world. The objective of this study was to evaluate tomato varieties for nematode and Ralstonia diseases resistance and productivity. The experiment was conducted under a complete randomized design experiment with three replications at Hawassa University shade house. Four varieties of tomato were inoculated with nematode (Meloidogyne incognita), Ralstonia solanacearum and mixed bacteria (Bacillus subtilis, Pseudomonas) in single and in combination of them with a total of six treatments. The multivariate analysis of variance showed a significant effect both for varieties and treatments for most yield and growth parameters except for unmarketable fruit yield per plant and weight of unmarketable fruit per plant. Tomato var. Venise produced the highest total yield (7556.33g) whereas Galilea variety gave the lowest total yield (2656.4g). Based on the yield performance, nematode and ralstonia resistance rating, Venise was found to be the best tomato variety followed by Awassa for disease resistance and productivity. Variety Galilea was severely affected by Meloidogyne incognita as well as by the Ralstonia solanacearum and produced the lowest marketable fruit percentage. None of the tomato varieties was found highly resistant (0 % disease severity) to Meloidogyne incognita and Ralstonia solanacearum. Therefore, there is a need to develop nematode and Ralstonia-resistant tomato varieties.